Kajian Emisi Gas Rumah Kaca (GRK) dari Perkembangan Teknologi Elektrifikasi Baterai Ponsel Pintar - Amrizarois Ismail (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2022)
Batteries as an energy source are no longer a known new technology; their use has been a part of life for many years. Batteries also have detrimental (bad) power, especially for the environment, including the contribution of carbon that produces Greenhouse Gas (GHG) emissions as one of the causes of global warming that triggers climate change. To find out, a quantitative study was conducted by calculating the energy conversion of smartphone batteries using the carbon conversion principle in the Intergovernmental Panel Climate Change (IPCC) formula. Based on the study's results, smartphone batteries use in the last decade has experienced a rapid increase starting from 60,431,616 tons of CO2 in 2011, and 2022 soaring to 447,672,960 tons of CO2. This shows a significant increase in GHG carbon emissions from smartphone battery development. and prove that the use of battery technology also produces carbon emissions from secondary sources and is not 100% environmentally friendly, therefore energy efficiency measures by using smartphones wisely are expected to reduce GHG carbon emissions due to the use of excessive battery power from smartphones.